Criminal Law Enforcement against Illegal Nickel Ore Mining (A Case at Resort Police of Kolaka Utara) - Jamarin Riche (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The crime of illegal nickel ore mining is a crime in the mining business carried out by individuals, groups of people, or companies/foundations with legal entities in which their operations do not have a legal permit from government agencies based on the applicable regulations threatened by the criminal sanctions for anyone who violates the prohibition. Article 38 of Law Number 3 of 2020 concerning Mineral and Coal Mining states that “Mining business actors include business entities, cooperatives, and Individuals.